Experimental study of RDF-5 performance based on natural waste on fast pyrolysis process on the quality of the liquid smoke - Herman Saputro; Laila Fitriana; Aris Purwanto; Riyadi Muslim; Muchlis Mahmuddin (Institute of Advanced Engineering and Science, 2023)
Energy problems are one of the cases faced by almost all countries in the world. No longer found oil reserves in significant quantities causing problems in the energy sector. The world's energy needs continue to increase and become a global problem in the use of energy in various sectors resulting in an energy crisis. The use of waste-to-energy (WtE) technology is appropriate, considering that energy needs continue to increase along with the increasing amount of waste that is not managed and hurts the ecosystem. Refuse-derived fuel (RDF) is a waste management technique that converts waste into bio-solid fuel. RDF is produced from the mechanical separation of combustible and non-combustible fractions from waste. Utilizing RDF biomass from durian peel and sugar palm is one of the efforts to maximize the pyrolysis process in organic waste, increasing the combustion potential. Processing durian skin and sugar palm waste into RDF will maximize the potential of the combustion results, which can later facilitate testing. This study also aims to utilize sugar palm waste and durian peel to have a use value as an alternative fuel. This research was an experimental study, fast pyrolysis was employed by using 300 grams both in durian and sugar palm, and the temperature was varied from 400, 500, and 600 °C. The results showed that the test of liquid smoke RDF-5 sugar palm at a temperature of 400 °C at 112 mL and RDF-5 durian at 600 °C at 137 mL.